Trauma Quality Indicators: Internationally Approved Core Factors For Trauma Management Quality Evaluation - Federico Coccolini; Yoram Kluger; Ernest E. Moore; Ronald V. Maier; Raul Coimbra; Carlos Ordoñez; Rao Ivatury; Andrew W. Kirkpatrick; Walter Biffl; Massimo Sartelli; Andreas Hecker; Luca Ansaloni; et al. (BMC, 2024)
Indexed by ERA